Multigrain Platinum Nanowires Consisting of Oriented Nanoparticles Anchored on Sulfur‐Doped Graphene as a Highly Active and Durable Oxygen Reduction Electrocatalyst. (22nd November 2014) - Hoque, Md Ariful; Hassan, Fathy M.; Higgins, Drew; Choi, Ja‐Yeon; Pritzker, Mark; Knights, Shanna; Ye, Siyu; Chen, Zhongwei
<x xml:space="preserve">Abstract</x> Direct growth of multigrain platinum nanowires on sulfur‐doped graphene (PtNW/SG) is reported. The growth mechanism, including Pt nanoparticle nucleation on SG, followed by nanoparticle attachment with orientation along the <111> direction is highlighted. PtNW/SG demonstrates improved Pt mass and specific activity compared with commercial catalysts toward oxygen reduction, in addition to dramatically improved stability through accelerated durability testing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>